Thermal condition of cohesion in a two-layer roll of a rolling mill (Моделювання, керування та інформаційні технології, 2019)
A condition of heat exchange between the layershaving different thermalphysic properties in a two-layercylindrical roll of a rolling mill is analyzed foe an ideal thermalcontact. It can be realized with application of the condition ofheat balance of one of the layers in the cylindrical area for ahomogeneous equation of heat conductivity. Analyzed was asimplified target setting in the radial section with a supposition,regarding an averaged in radius temperature distribution in theouter layer. By applying the condition of the thermal balance andby integrating the homogeneous equation of heat conductivity inthe two-layer area a condition of cohesion of an impedance typein case of an ideal thermal contact between the layers wasconstructed.